Measurement of multi-scale deformation of polycarbonate using X-ray scattering with in-situ loading and digital image correlation. (15th January 2016) - Engqvist, Jonas; Wallin, Mathias; Hall, Stephen A.; Ristinmaa, Matti; Plivelic, Tomás S.
Abstract: Deformation of amorphous, glassy polycarbonate (PC) is characterised over a wide range of length-scales using spatially-resolved wide angle X-ray scattering (WAXS) with simultaneous digital image correlation and in-situ uni-axial loading. Novel observations are presented on the correlation of the evolution of the molecular structure linked to the relevant local macroscopic measures of strain as the sample deforms. This provides new insights into the mechanisms of deformation in amorphous, glassy polymers. Strains and evolving anisotropy are observed, and quantified, at different length scales identified from the WAXS measurements connected to inter- and intramolecular structures. The inter-molecular structures show permanent deformations in the form of unrecoverable stretches and reorientations, whilst intra-molecular structures show recoverable strains and unrecoverable reorientations. Such insights pave the way for development of enhanced constitutive models for amorphous glassy polymers with a correct micro-mechanical basis and calibrated evolution of anisotropy. Graphical abstract: Highlights: The deformation of glassy polycarbonate is measured over a range of length-scales. Wide angle X-ray scattering is used with in-situ loading and image correlation. Molecular strain and reorientation is measured using wide angle X-ray scattering. Elastic deformation is measured within the polymer chain segments. Permanent macroscopic deformation is coupled to reorientation of the chain segments.